Including Legumes in Bermudagrass Pastures - J. L. Moyer; L. W. Lomas (Kansas Agricultural Experiment Station Research Reports, 2016)
Use of legumes in bermudagrass pastures has often increased summer cow gains. Forage production was greater where ladino clover was used in the Legume system than where Nitrogen (N) alone was used in the first sampling, but the reverse was true in midsummer. Estimated forage crude protein during 2015 was greater for the Legume than the Nitrogen system in the first and last samplings, but similar in mid-summer pasture. Cow performance over the season was increased 68% where legumes were used.
Keywords: pastures; beef cattle